Security in Smart Home Development: A Review (International Journal of Innovative Research in Computer Science & Technology, 2021)
A clever home or structure is a modern  house or construction with special organized wiring that  enables residents to control or program a variety of  automatic household electrical devices remotely with a  single order. Traditional security systems keep intruders at  bay, keeping homeowners and their valuables safe. On  either hand, a smart house protection system offers a host  of extra benefits. Home automation technology notifies  homeowners of possible problems, allowing them to  investigate. This article discusses smart houses and  security, as well as a smart home security technology.  Whether you give your command by voice, tv remote, or  computer, the home will fulfill it. The most popular uses  include light, home protection, house theater and  entertainment, and temperature adjustment. Security has  been a serious worry in smart home technologies.
Keywords: Automation; Protection; Smart Home; Security